Beer and Brewing in Medieval Culture and Contemporary Medievalism - Geck, John A.; O'Neill, Rosemary; Phillips, Noelle (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Representations of Beer in the Middle Ages: Beer Culture and Medievalisms is a cross-cultural analysis of the role that alcohol consumption played in literature, social and cultural history, and gender roles in the Middle Ages. The volume also seeks to correct or offer new insights into historical beer production. By drawing on the expertise of scholars of history, archaeology, Old and Middle English, Old Norse, and Medieval and Early Modern literature, the book produces a sustained discussion of how beer and alcohol consumption in the Middle Ages directly contributes to the romanticized vision of the medieval ale-hall omnipresent in beer marketing today. The essays describe alcohol consumption in the Middle Ages across much of Northern Europe, engage with the various myths employed in modern craft beer advertising and beer production, and examines how gender intersects with beer production and consumption. The editors also raise certain critical questions about medievalisms which need to be interrogated, particularly in light of the continued use of the Middle Ages for white supremacist and colonialist ideals. The volume contributes to the study of the popular and historical understandings of the Middle Ages as well the issues of race and gender. John A. Geck is Assistant Professor in the Department of English at the Memorial University of Newfoundland, Canada, where his research deals with transmissions of high and low culture in later medieval and early modern England, encompassing romance, hagiography, and drama; medievalisms and other projections of the medieval in popular and digital culture. Rosemary O'Neill is Associate Professor of English and Women's and Gender Studies at Kenyon College, USA. Her research explores the intersection of economics and medieval literature, and she has published and forthcoming work on Langland; Chaucer; the figure of Judas in medieval drama and poetry; and the resonances of medieval poetry in contemporary literature. Noelle Phillips is English Instructor at Douglas College, Canada. Her research engages in medieval book history, the work of Chaucer and Langland, the book collecting habits of the Earls of Northumberland, and most recently, the use of medievalism in marketing craft beer and breweries. Her recent book, Craft Beer Culture and Modern Medievalism: Brewing Dissent (2019) explores the stories and mythologies inherent to modern craft brewing. .
Part I: Brewing (historical perspectives on the production of beer and ale in Medieval Europe) -- Conan Doyle, Ale and Beer in Early Medieval England: A Survey of Evidence -- Mark Edwin Peterson, Reliving the Drink: The Difficulties of Medieval Beer History versus the Desire for Historical Beer -- Susan Verberg, Reconstructing medieval gruit ale: separating facts from fiction -- Part II Drinking (on the cultural meanings of beer in the Middle Ages; medieval drinking culture) -- Richard Fahey, The Wonders of Ebrietas: Drinking in Anglo-Saxon Riddles -- Fernando Guerrero, Sacred Beer: Pre-Christian Cultural and Economic Perceptions of Alcoholic Beverages in Medieval Norwegian and Icelandic Liturgy -- Randy Schiff, Alcohol, Community, and Chaucer's Pardoner: Ale as a Populist Antidote to Alienating Avant-Gardism -- Part III: Gender (on beer and women.) -- Rosemary O'Neill, Devil's Brew: Alwives and the Medieval Antecedents of Infernal Imagery in Contemporary Beer Marketing -- Carissa M. Harris, From Tapsters to Beer Wenches: Women, Alcohol, and Misogyny Then and Now -- Rebecca Straple, 'Far From Drunk With Ale': Women, Alcohol, and Power in Old Norse-Icelandic Literature -- Part IV Ludic Medievalism (on the Middle Ages as a space of play in modern perceptions of beer) -- Noelle Phillips, Playing with Vikings: Ludic Medievalism in Norse-Themed Breweries -- Anna Czarnowus,'Harsh, violent, muddy,' or Ale and Beer in Adam Thorpe's Hodd -- Part V Nostalgic Medievalisms (on uses of the medieval past in the context of beer to bolster nationalist projects) -- Mary Bateman, Nostalgic medievalism in Peter Mews' Ex-Ale-Tation of Ale (1663) -- John A. Geck, Codex Cervisarius: A Pilgrim's Guide to the Medievalism of Craft Beer in Quebec and Ontario -- Robert Saunders, Latvia's Labietis: Modern Craft Brewing across the Pagan-Christian Threshold -- Donovan Tann, 'God wotte what liquor': Brewing History and Memory in Early Modern England -- Afterword.
Keywords: Literature, Medieval; Popular Culture; Europe-History-476-1492.; Comparative literature; Literature-History and criticism; Medieval Literature; Popular Culture; History of Medieval Europe; Comparative Literature; Literary History